Big Data, Scapegoat or Hero – Ethical Insights from René Girard - Harris, Howard (Who's watching? Surveillance, big data and applied ethics in the digital age, 2022)
Big Data draws both praise and criticism, seen as both villain and hero. The release of megabytes of data by Wikileaks is accorded praise as information transparency by some, whilst others find the massive collection of information by Amazon or Google, often freely given, immoral and to be feared. The paper examines three cases embracing the velocity, volume and variety aspects of Big Data – digital platforms, driverless cars and the Banking Royal Commission – and uses René Girard’s theories of mimesis and scapegoating to show that the identification of a scapegoat, or villain, is a common feature in them and that concerns over Big Data are linked to fear of ‘the other’, thus helping to show how Big Data can be both loved and hated and how both practitioners and theorists might comprehend public reaction to big data and its ethical dimensions.